Pag- ahon an adaptive floating community against sea level rise in Barangay Alaska, Aringay, La Union - Valenzuela, Julienne L.
Climate change continues to shift the landscape of our natural and built environment. The ecological changes come in many forms such as sea-level rise. In the Philippines alone, low-lying coastal communities are being affected by the rising sea waters. The effects can mean destruction of land, displacement of communities, or, worse, loss of lives. Even though conventional solutions are being made, most often these are carried out without the participation of the various stakeholders and without the assessment of multifaceted social, economic, and cultural factors. In addition, the susceptibility to climate change especially in the country's seaside areas is generally heightened by the shortage of infrastructure, dilapidation of the natural environment, and mounting problems aggravated by other factors. As a coastal community, Barangay Alaska in Aringay, La Union, experiences first-hand the effects of sea-level rise. The community is at risk of losing their land and livelihood. As such, this project addresses this by providing an alternative architectural solution through the application of various approaches, innovations, and development programs to adapt to sea-level rise. The project design integrated the concept of floating architecture in creating a socialized housing complex with the addition of facilities that promote economic growth and social integration in the community.